ANALISIS FAKTOR HEAD LOSSES PENSTOCK TERHADAP DAYA YANG DIHASILKAN DI PLTA SAGULING - Irfan Muhamad Ramadon; Adi Syuriadi (Politeknik Negeri Jakarta, 2016)
ABSTRACTHydroelectric Power Plant (PLTA) / Hydroelectric Plant is a plant that rely on the potential and kinetic energy of water to generate electricity, which is referred to as Hydroelektrik. The general form of this type of power plant is connected to a turbine generator that is driven by the kinetic energy of the water. One civilian buildings in hydropower is penstock. Rapid pipe (penstock) is a pipe that has a closed flow. Fluid flow in the pipeline is closed, both types of laminar or turbulent, definitely head losses (head losses) that will influence of the power generated at each plant unit.Water entering the penstock have a discharge 202 m3 / s (data source UP Saguling Month April 2016) with the first penstock length of 1868.189 m and the second penstock of 1768.429 m and a diameter varying of 4.3 m; 2.83 m; 2.25 m which would affect the value of the flow velocity, Reynolds number, as well as the value of the friction factor .From The penstock length of both artifacts losses (head losses) generated due to the friction of water on the surface of the penstock (major losses) and the result of fitting / valve that exist along the penstock (minor losses) that would have a relationship with the power generated at each unit in the plant.After going through the calculation of head losses in discharge 202 m3 / s, the obtained results, the value of head losses total at penstock 1 for Unit 3 and Unit 4 are 45.482 m and 45.179 m as well as on pesntock 2 for unit 1 and unit 2 are 43.644 m and 43.333 m , Factors head losses in each unit having an influence on power generated. The bigger the head losses generated value, the smaller the power generated. So that the relationship between the head losses penstock and the power generated by each unit inversely.Keywords: Penstock, Head Losses, Major Losses, Minor Losses, Power.ABSTRAKPembangkit Listrik Tenaga Air (PLTA) / Hydroelectric Plant adalah pembangkit yang mengandalkan energi potensial dan kinetik dari air untuk menghasilkan listrik, yang disebut sebagai Hydroelektrik. Bentuk umum dari pembangkit listrik jenis ini adalah generator yang dihubungkan ke turbin yang digerakan oleh tenaga kinetik dari air. Salah satu bangunan sipil yang ada di PLTA adalah penstock. Pipa pesat (penstock) merupakan sebuah pipa yang memiliki aliran tertutup. Aliran fluida yang ada di dalam saluran pipa tertutup, baik itu jenis laminer maupun turbulen, pasti mengalami kerugian head (head losses) yang akan mempengaruhi dari daya yang dihasilkan pada setiap unit pembangkit.Air yang masuk ke penstock memiliki debit 202 m3/s (sumber data UP Saguling Bulan April 2016) dengan panjang penstock pertama sebesar 1.868,189 m dan penstock kedua sebesar 1.768,429 m serta diameter yang berbeda-beda yaitu 4,3 m; 2,83 m; 2,25 m yang akan mempengaruhi nilai kecepatan aliran, bilangan Reynold, serta nilai faktor gesekan.Dari panjang kedua penstock tersebut tedapat rugi – rugi (head losses) yang dihasilkan dikarenakan adanya gesekan air terhadap permukaan penstock (major losses) dan akibat dari fitting / valve yang ada di sepanjang jalur penstock (minor losses) yang akan memiliki hubungan dengan daya yang dihasilkan pada setiap unit di pembangkit.Setelah melalui perhitungan head losses pada debit 202 m3/s maka didapatkan hasil, nilai head losses total pada penstock 1 untuk unit 3 dan unit 4 sebesar 45,482 m dan 45,179 m serta pada pesntock 2 untuk unit 1 dan unit 2 sebesar 43,644 m dan 43,333 m. Faktor head losses di masing-masing unit memilik pengaruh terhadap daya yang dihasilkan. Semakin besar nilai head losses yang dihasilkan maka semakin kecil daya yang dihasilkan, begitupula sebaliknya. Sehingga hubungan anatar head losses penstock dan daya yang dihasilkan setiap unit berbanding terbalik.Kata kunci: Penstock, Head Losses, Major Losses, Minor Losses, Daya.